Students' Interest in Participating in Sports Extracurricular Activities at SMA Negeri 2 Tenggarong - Fauzi, Muhammad Sukron; Cahyono, Didik; Naheria, Naheria; Cahyaningrum, Gyta Krisdiana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
High school students generally participate in activities based on encouragement or invitations without fully understanding the purpose behind them. In reality, individuals typically engage in certain activities driven by personal interest. In this context, interest becomes a component of personality that plays a role in influencing students' choices. The purpose of this study is to determine the level of student interest in participating in sports extracurricular activities at SMA Negeri 2 Tenggarong. This research is a quantitative descriptive study using a survey method. The research subjects were students who do not participate in sports extracurricular activities at SMA Negeri 2 Tenggarong, totaling 719 students. The instrument used was a questionnaire, with a reliability coefficient calculated using Cronbach’s Alpha formula, resulting in a value of 0.901. Quantitative descriptive statistics with frequency tables were used to analyze the data. The results showed that students' interest in participating in sports extracurricular activities at SMA Negeri 2 Tenggarong tends to fall within the moderate category. The results are detailed as follows: very high category – 9.19%, high category – 19.5%, moderate category – 33.3%, low category – 25.29%, and very low category – 12.6%.